Transarterial chemoembolization combined with sorafenib for advanced hepatocellular carcinoma - SHAO, WENBO (D.A. Spandidos, 2014)
Sorafenib has been demonstrated to improve survival rate in patients with advanced hepatocellular carcinoma (HCC); however, the survival benefit remains modest and the response rates remain poor. Transarterial chemoembolization (TACE) may be used for the treatment of advanced HCC with well-preserved liver function and has a high local tumor control rate. We hypothesized that patients with advanced HCC may benefit from the combination of sorafenib with TACE. A retrospective study was conducted involving patients with advanced HCC, who had received at least one TACE session. Patients subsequently received 400 mg sorafenib twice per day and were monitored monthly. A dose reduction from 400 to 200 mg of sorafenib twice per day was permitted. The overall survival and side effects were subsequently followed up. In total, 38 patients were included from April 1st, 2009 to March 31st, 2012. All patients were treated with sorafenib after TACE was performed. As of March 31st, 2013, seven patients remained on sorafenib, and were censored at that time point. The median overall survival time was 12 months (95% confidence interval, 6.3–17.7 months). The sorafenib dose was reduced temporarily in 32 patients (84.2%). The most common toxicities were dermatological adverse effects (94.7%), diarrhea (63.2%) and alopecia (26.3%). The survival benefit of sorafenib combined with TACE for advanced HCC is promising, with no intolerable adverse events, provided that dose adjustment is permitted.